A Comparative Study of Temporalis Fascia Graft and Cartilage - Perichondrium Graft in Tympanoplasty - Shaden Zakariya Yahya Al Riyami; Ammar Al Lawati; Subirendra Kumar (Journal of Otolaryngology Advances, 2025)
Objective The repair of the tympanic membrane has been attempted with large variety of synthetic, homologous and autologous tissue; however, temporalis fascia and cartilage-perichondrium are used most commonly today. Study Design This is a prospective study of patients confirmed to have CSOM and operated during the years of 2012-2013 at Al Nahdha Hospital, Muscat, Sultanate of Oman. The patients were followed up postoperatively at which we compared the graft success rate and level of hearing improvement. Setting ENT clinic at Al Nahda hospital Subjects Patients who presented to the ENT clinic at Al Nahda hospital, operated in the period between 2012 and 2013, diagnosed as CSOM and meeting our inclusion criteria. Methods We compared the outcome of the repair of the tympanic membrane perforation using temporalis fascia graft versus cartilage perichondrium grafts. Results 100% of the cartilage-perichondrium group showed a successful graft uptake in comparison to 98.9% in the temporalis fascia. Our data did not show significant differences in the average air bone gap change in both groups. Conclusion Both cartilage-perichondrium and temporalis fascia provide viable autograft material. Both achieve comparable and excellent graft uptake. Completion of our study is needed to study the hearing restoration in both groups.
Keywords: Tympanoplasty